A Rapid Method to Aromatic Aminoalkyl Esters via the Catalyst-Free Difunctionalization of C–N Bonds - Zhu, Qiming; Yang, Peng; Chen, Mingwei; Hu, Jinyu; Yang, Luyi (Synthesis, 2018)
A novel multicomponent reaction involving a direct C–N esterification/arylation has been developed. This catalyst-free process was conducted with cyclic tertiary amines via a facile C–N cleavage to provide the alkyl group and nitrogen source. The operationally simple method to rapidly combine cyclic tertiary amines, haloazaarenes and carboxylic acids (or anhydrides) affords an efficient access to aromatic aminoalkyl esters, potential drug-like products, in good to excellent yields.
Keywords: multicomponent reaction; C–N cleavage; esterification; arylation; catalyst free